Application of Problem Solving in Improving Learning Outcomes of Sociology Concepts of Values and Social Norms at SMA Al-Fiqri Telaga Piru, West Seram District, West Seram Regency - Meilisa Meilisa; H. Abarua (Peneliti.net, 2022)
The purpose of this study is to improve learning outcomes of Sociology Concepts of Values ​​and Social Norms at SMA Al-Fiqri Telaga Piru, West Seram District, West Seram Regency where teachers are fully involved in research starting from planning, action, observation, and reflection. The method used is classroom action research (CAR). The results of the study indicate that: that the application of the problem solving can improve teaching and learning activities. Through the Problem Solving, students can arrange and explain pictures logically and build their own knowledge, think together and find steps in finding solutions to the material that must be mastered by students, either individually or in groups. The ability of students in group discussions has progressed very well, this can be seen from students who have started to get used to studying in groups. The mastery of students in learning material concepts of Values ​​and Social Norms is seen from the average learning outcomes of students who have increased each cycle. In the first cycle, the percentage of student learning outcomes is quite good at 33.33% and for the second cycle the percentage of student learning outcomes is very good by achieving the minimum completeness criteria of KKM > 75 by 83.33%.